Calidad de cuidado del profesional de enfermería y satisfacción del paciente adulto hospitalizado - Quispe Gamboa, Vanessa Antonella (2017)
The present quantitative, cross - sectional descriptive study was performed with the purpose of knowing the quality of care of the nursing professional perceived by the hospitalized adult patient and satisfaction at the Leoncio Prado - Huamachuco Hospital. The sample consisted of 71 adult patients, who met the established inclusion criteria. The information was obtained through the Survey on the level of quality of nursing care and Survey of level of satisfaction perceived by the patient. The obtained results were tabulated and presented in tables of one and double entry, in numerical and percentage form. For the statistical analysis, the Independence test of Chi square criteria (X²) was applied, with a level of significance lower than 5 percent (p <0.05). From the results it was concluded that 4.2% of hospitalized adult patients perceive a low level of quality of care of the nursing professional, 84.5% average level, while 11.3% perceive an optimal level. In addition, 1.4% of hospitalized adult patients have a low level of satisfaction, 85.9% mean level, and 12.7% high satisfaction level. Also, 77.5% of hospitalized adult patients perceived an average level of nursing care quality and average level of satisfaction. This means that the quality of care of the nursing professional is directly related to the satisfaction of the hospitalized adult patient, this shows the highly significant relationship between the study variables.